IMPLEMENTASI KONSEP PLURALITAS DALAM FILM “CAHAYA DARI TIMUR BETA MALUKU” (SEMIOTIKA ROLAND BARTHES) - Nurul Huda Awalia Mataniari, Muhammad Husni Ritonga, Indira Fatra Deni Pa (At-Tazakki: Jurnal Kajian Ilmu Pendidikan Islam dan Humaniora, 2022)
Abstract: The purpose of this study is to find out how the concept of plurality is in the film "Cahaya dari Timur Beta Maluku". This research uses qualitative research with descriptive approach and Roland Barthes semiotic approach. The data collection techniques by conducting observations, documentation and literature study. The primary data source is film video recordings. The findings of this study are three forms of the concept of plurality and its implementation in the film "Cahaya Dari Timur Beta Maluku" namely religious plurality, plurality of places and plurality of languages which are analyzed using Roland Barthes' semiotics model by looking for the denotative, connotative and mythical meanings of each element. symbol in the picture. Keywords: Plurality Concept, Semiotics Roland Barthes